MODEL VALUE OF RESIDUAL STRENGTH OF CONCRETE ASPHALT PAVEMENT CONSEQUENCES OF SOAKING OF RAINWATER AND SEAWATER BY CONTINUOUS AND PERIODIC METHODS - Oloan Sitohang; Asmirus Laia; Edison Hatoguan Manurung; Sarjono Puro (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2023)
High rain intensity and limited draninase capacity result in high waterlogging on the road surface for a long time. After dry inundation, the pavement surface undergoes a bond between the aggregate and loose asphalt. This loose condition, when crossed by vehicles, causes cracks and holes so that the road is damaged. In addition, large-scale waterlogging can cause groundwater located below the soil surface to become saturated. The research method is an experimental laboratory with the help of descriptive statistics in analyzing data to find out an overview of the characteristics of concrete asphalt mixture materials. Penelitian aims to: Knowing the relationship between variations in soaking duration to the durability performance of asphalt concrete mixtures, Evaluating differences in residual strength index values due to length soaking by using seawater and rainwater with continuous and periodic mrtode, and Determining the relationship model between the Residual Strength Bonding of the asphalt mixture to time of soaking seawater and rainwater. The residual strength bond value (IKS) is greatly influenced by the soaking time, where the longer the concrete asphalt issoaked, the significantly lower the IKS value. As for the Modelh the difference between the Residual Strength Index against the bath time is a polynomial model.